Mind Warmups-11

Calculus Level 4

Let g ( x ) g(x) be a function satisfying g ( x + 1 ) + g ( x 1 ) = g ( x ) g(x+1)+g(x-1)=g(x) . What is the period of g g ?

g g is not periodic. 3 6 2

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Chew-Seong Cheong
Sep 21, 2018

Given that

g ( x + 1 ) + g ( x 1 ) = g ( x ) g ( x + 1 ) = g ( x ) g ( x 1 ) g ( x + 2 ) = g ( x + 1 ) g ( x ) = g ( x ) g ( x 1 ) g ( x ) g ( x + 2 ) = g ( x 1 ) g ( x + 2 + 3 ) = g ( x 1 + 3 ) g ( x + 5 ) = g ( x + 2 ) = g ( x 1 ) g ( x + 6 ) = g ( x ) \begin{aligned} g(x+1) + g(x-1) & = g(x) \\ \implies g(x+1) & = g(x) - g(x-1) \\ g(x+2) & = g(x+1) - g(x) \\ & = g(x) - g(x-1) - g(x) \\ \implies g(x+2) & = - g(x-1) \\ g(x+2+{\color{#D61F06}3}) & = - g(x-1+{\color{#D61F06}3}) \\ g(x+5) & = - g(x+2) = g(x-1) \\ \implies g(x + {\color{#3D99F6}6}) & = g(x) \end{aligned}

Therefore, the period of g g is 6 \boxed 6 .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...